Comparison of the modelled and measured mass balance of the Central Tuyuksu glacier, northern slope of Ili-Alatau (ҚазҰУ Хабаршысы. География сериясы, 2025)
The study considers the results of numerical modeling of the mass balance of the Central Tuyuksu Glacier, located on the northern slope of the Ile Alatau, Northern Tian Shan, using the DMBSim model. A comparison was conducted between the computed values of both winter and annual mass balances and the measurements obtained during the balance years of 2006-2023. The input data for the modeling included data on glacier accumulation, ablation, and mass balance derived from stakes, as well as snow surveys with pit measurements. Additionally, air temperature and precipitation data from the Tuyuksu weather station and total precipitation gauges were incorporated.The largest difference between the simulated winter mass balance and the measured values on actual dates was observed during the 2006/07 period, amounting to 0.37 m w.e. (68%), with an average of 0.17 m w.e. (29%). The maximum disparity in annual mass balance, also on actual dates, was 0.34 m w.e. (40%), with an average of 0.05 m w.e. (9%). These findings provide valuable data for use in predictive calculations for the surface mass balance and glacier runoff.